Inclusión del tercero civil responsable y debido proceso - Quispe-Ayala, Cesar; Cuevas-Montes, Franklin; Godoy-Huamán, Yaneth; Marquez-Ichpas, Elvis (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of an investigation presented to the Private University of Ica, whose objective was to determine the inclusion criteria of the civil third party responsible for the protection of due process, from the point of view of the ICA Criminal Judiciary. Since a problem is present in our punitive procedural reality that harms one of the parties that intervenes in the process, such as the responsible civil third party, it is the moment of its incorporation into the process, because each judiciary performs an exegesis on its configuration legal, specifying that this must be before the culmination of the preparatory investigation stage, at the beginning of the preparatory investigation, identified the active subject of the criminal act, raising questions, because there is a violation of fundamental rights, especially with respect to the right to defending. The object of discussion in the doctrine and jurisprudence and that the controversy remains without making substantive changes through a legislative amendment, a plenary agreement or another legislative measure that leads to correct people who are tried without having committed a crime. The research was of a quantitative approach considering the doctrine and the criminal and constitutional procedural jurisprudence on the subject. As well as the reading of the connoisseurs of the problem through the application of the survey with lawyers and operators of the criminal judiciary.